Web Camera Application For Motion Detection - Koay, Su Yeong (2003)
Motion detection is the ability to recognize the presence of movements. There are many different ways to detect motion. The conventional way is by using either active sensor or passive sensor. The new method to detect motion is "vision motion detection". It is the artificial way of machine vision system compared to human's vision in detecting motion. Motion detection is the most important feature in digital video surveillance system. It gives the camera the capability to capture when needed rather than capture all the time and this leads to huge reduction in storage space. Alarm can also be triggered when unexpected motion is detected. This relieves the personnel in monitoring at all time.This thesis presents the design and implementation of a low cost security system. The system consists of only a web camera and a personal computer, which is incorporated with motion detection capability. The motion detection capability is using the concept of "motion detection by vision". Therefore no hardware sensors like active sensor and passive sensor are required. The motion detection capability provided in this system is derived from image subtraction method. This thesis project consists of three main stages, namely hardware setup, simulation and implementation. The first stage is setting up the system of which consists of PC and web camera. The web camera is only operable with the web camera driver installed in the PC. In the second stage, simulation done on the frame images using Matlab with Image Processing Toolbox as simulation tool to investigate the possibilities of motion detection algorithm on images captured by web camera. In the third stage, implementation process is done by coding the motion detection software using Microsoft Visual Basic 6.0. The algorithm that was successfully simulated is used as the reference for forming the working mechanism in creating motion detection software. This self-created motion detection software is then installed and run on the PC to function as a complete intelligent motion detection system.